Robust Interactive Video Transmission in MC-CDMA Cellular Networks over Slow Fading Channels DOI: 10.14209/jcis.2003.20 - R. Hueda, Mario; E. Rodríguez, Carmen (Journal of Communication and Information Systems, 2015)
Reliable interactive video transmISSIon in COMA cellular networks is difficult because residual channel errors (after error correction) cannot be completely eliminated and the available bandwidth is scarce. To improve the quality of the decoded video. this paper introduces a novel architecture for low bit rate transmission in multicode OS-CDMA (MC-COMA) cellular systems. Unlike previous protection schemes, the new architecture not only improves video quality, but it also achieves an efficient use of the available resources in the network. As an application of this concept, we propose a robust scheme for reliable video communication from wired to mobile users in slow fading environments. This scenario has been shown to be the most critical owing to long block error bursts present in the forward link of COMA systems where closed-loop power control is not used (such as IS-95B), and the inability of error resilience approaches incorporated in wired video codecs to guarantee an acceptabk video quality in wireless transmissions. Our approach consists of two main ingredients: (i) a novel closed-loop error control technique to reduce packet loss, delays, and interference, and (ii) a new scheme to stop error propagation in the decoded sequence originating from residual channel errors. Based both on theoretical analysis and numerical results, we show thaI our approach achieves important improvements in the quality of the decoded video. Furthermore, we show that the new architecture oUlperforms previous error protection schemes with low additional complexity.